The anti-senescence effect of resveratrol reduces postharvest softening rate in cherimoya fruit - Morales Pérez, Aaran Aquilino (2014)
Due to its climateric behavior, the cherimoya fruit (Annona cherimola Mill.) is a very perishable commodity. Present research aimed to observe the anti-senescence effect of resveratrol (RVS); this plant bioregulator was applied at 1.6, 0.16, 0.016 and 0 mM at 0, 8 and 15 days before harvest (DBH). At 1, 7 and 15 days of postharvest life, several physical and biochemical determinations were performed on the cherimoya fruit. After 15 days under room temperature conditions, in relation to control fruit, those fruit with 1.6 mM RVS applied 15 DBH reduced skin softening rate 78% and 54% for Fino de Jete and Bronceada, respectively. Similarly, after 15 days of storage, a non-trained group of tasters preferred those fruit treated with 1.6 mM RVS 15 DBH; they qualified the fruit as better than the control fruit in presentation, aroma and taste.